2008
DOI: 10.1016/j.micinf.2008.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific oxidative imbalance and mitochondrial dysfunction during Trypanosoma cruzi infection in mice

Abstract: In this study, we examined the tissue specificity of inflammatory and oxidative responses and mitochondrial dysfunction in mice infected by Trypanosoma cruzi. In acute mice, parasite burden and associated inflammatory infiltrate was detected in all tissues (skeletalmuscle>heart>stomach>colon). The extent of oxidative damage and mitochondrial decay was in the order of heart>stomach>skeletal-muscle>colon. In chronic mice, a low level of parasite burden and inflammation continued in all tissues; however, oxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 28 publications
5
79
0
1
Order By: Relevance
“…A persistence of oxidative stress in chronic chagasic hearts when the parasite burden is present at the minimal level has also been noted (15,17) and suggested to intensify cardiomyocyte necrosis and cardiac contractile dysfunction (reviewed in reference 41). Our observation of activation of the oxidative/nitrosative burst along with a proinflammatory cytokine response and tissue migratory properties in M incubated with sera of chagasic mice provides the first indication that a feedback cycle of M activation by circulatory factors might contribute to chronic inflammation and oxidative damage in Chagas disease.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A persistence of oxidative stress in chronic chagasic hearts when the parasite burden is present at the minimal level has also been noted (15,17) and suggested to intensify cardiomyocyte necrosis and cardiac contractile dysfunction (reviewed in reference 41). Our observation of activation of the oxidative/nitrosative burst along with a proinflammatory cytokine response and tissue migratory properties in M incubated with sera of chagasic mice provides the first indication that a feedback cycle of M activation by circulatory factors might contribute to chronic inflammation and oxidative damage in Chagas disease.…”
Section: Discussionmentioning
confidence: 92%
“…We have recently shown that prophylactic vaccination before challenge infection (11)(12)(13)(14) or treatment of chronically infected experimental animals with the antiparasite drug benznidazole (15), which resulted in the host's ability to control acute parasitemia and tissue parasite burden (11)(12)(13)(14), consequently prevented myocardial oxidative and inflammatory pathology (15)(16)(17) and led to preservation of the hemodynamic function of the heart (15). Because oxidative/inflammatory adducts result in cellular damage, we hypothesize that the damage-associated molecular patterns (DAMPs) are released in the peripheral blood and can be captured by the phagocyte activation pattern.…”
mentioning
confidence: 99%
“…We have shown that T. cruzi infection results in increased carbonyland 3NT-modified proteins and MDA in the myocardium and plasma of infected mice (13,40) and rats (unpublished data) and contributes to mitochondrial electron transport chain dysfunction (39) and altered cardiac hemodynamics in the infected host (unpublished data). The oxidative/nitrosative stress in infected animals was exacerbated due to compromised glutathione antioxidant defense capacity and resulted in an inefficient scavenging of free radicals (42). The extent of protein modification in the heart and plasma of infected animals was correlated with the magnitude of inflammatory responses (13), which was suggestive of a role of inflammatory responses in sustaining oxidative/nitrosative stress during progressive Chagas' disease.…”
Section: Vol 16 2009 Indicators Of Inflammation In Chagas' Disease 663mentioning
confidence: 97%
“…The changes in immune response, oxidative stress, and antioxidant imbalance are detectable in peripheral blood of infected mice (20), and, notably, a strong positive correlation was detected for the disease state-specific changes in the heartversus-blood level of oxidative stress markers and antioxidants (e.g. glutathione peroxidase, glutathione, and manganese superoxide dismutase) (20).…”
mentioning
confidence: 99%